PENINGKATAN MOTIVASI BELAJAR MAHASISWA MELALUI PEMANFAATAN MEDIA SAMPAH SEBAGAI BAHAN DASAR KOLASE - Iqnatia Alfiansyah (JUSEDA, 2020)
The background of this research is the low of student motivation on study in University of Muhammadiyah Gresik. It was caused of the learning process conducted monotonous and not to use learning media. The purpose of this research are to up student’s motivation in learning process. This research applied class action research method which was used data analysis technique of descriptive qualitative and quantitative. The instrument is the response of students. Student’s motivation showed the good results to the learning process, there are 88,6%. The conclusion of this research that using rubbish for creativity can increasing student’s motivation on studies in University of Muhammadiyah Gresik.